The Status of Women in War: A Bibliometric Analysis - Obeidat, Bilal Fayiz; AlKhaza’leh, Mohammad Salman; Haimed, Saber (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to provide a comprehensive bibliometric analysis of research on the status of women in the context of war. Despite the richness of literature on armed conflicts, there has been less systematic evaluation of the research output concerning this important gendered dimension of war. Methods: The study draws on 187 articles retrieved from the Scopus database, using the phrase "The status of women in war" in the search query to identify relevant publications. A bibliometric analysis was conducted to examine the patterns in publication productivity across countries, citation impact, key sources, affiliations, authorship trends, and thematic keywords. Results: The findings reveal a gradual increase in research outputs related to women and war over the past three decades, with notable spikes following major conflicts in the 21st century. However, the citation impact of this work has decreased over time. The analysis also highlights the dominance of scholarship from Western countries, indicating the need to incorporate diverse global perspectives. Conclusions: The paper concludes that while scholarship on women's gendered experiences of conflict is expanding, critical gaps remain in equitably representing diverse voices and contexts. Prioritizing interdisciplinary, intersectional analyses through collaborative global networks is needed to elevate overlooked perspectives for a comprehensive understanding of the urgency of women's realities in war.